Evaluation of a group of Elderly in the neighborhood Butantã (SP) in the supposed fear of falling - Galimberti, Jacqueline Zanatta (2013)
The aging process is accompanied by problems of physical and mental health caused often by chronic diseases and falls. Objectives: To identify the alleged fear of falling while performing activities of daily living in an elderly group. Material and Methods: A descriptive approach, a cross-sectional study using the Brazilian version of the questionnaire translated by Camargo (2007). Will be interviewed 20 elderly aged 60 or older, residents of the neighborhood Butantã (SP) randomly. Results: For fear of falling show most seniors avoid in performing certain activities.